Carbon nanotubes: do they toughen brittle matrices? - Cho, Johann; Inam, Fawad; Reece, Mike J.; Chlup, Zdenek; Dlouhy, Ivo; Shaffer, Milo S. P.; Boccaccini, Aldo R. (Journal of Materials Science, 2011)
The development of a model CNT-brittle matrix composite system, based on SiO2 glass containing well-dispersed CNTs at up to 15 wt%, allows a direct assessment of the effect of the nanoscale filler on fracture toughness (KIC). Samples were prepared by colloidal heterocoagulation followed by spark plasma sintering. Detailed KIC measurements, using both indentation and notched beam techniques, show a linear improvement with CNT content, with up to a twofold increase of fracture toughness at maximum loading. The results from the two methods used in this study show equivalent trends but differing absolute values; the relative merits of these two approaches to measuring nanocomposite toughness are compared. Possible toughening mechanisms associated with CNT pull-out, crack bridging, and crack deflection are identified, and discussed quantitatively, drawing on conventional short-fibre composite theory and the potential effects of scaling fibre diameter. © Springer Science+Business Media, LLC 2011.
UnivIS-Import:2015-03-09:Pub.2011.tech.IW.LM.carbon